THE EFFECTS OF THE COVID-19 PANDEMIC ON PHYSICAL ACTIVITY LEVELS IN ADOLESCENTS - Agapii Eugeniu; Savițchi Svetlana (Sport şi Societate)
The COVID-19 pandemic has had a considerable impact on the lifestyle and physical health of adolescents, directly affecting body mass index (BMI) and physical activity levels.The aim of this study is to analyze and assess the impact of the COVID-19 pandemic on body massindex (BMI) and physical activity levels among adolescents, with the goal of identifying the determinants and long-term consequences on their physical health. The hypothesis of this study hypothesizes that the COVID-19 pandemic has exerted a significant negative influence on body mass index (BMI) and physical activity levels among adolescents. It is anticipated that this phenomenon will lead to high levels of sedentary lifestyles and an increase in the prevalence of overweight among this demographic group.Results. The study revealed significant improvements in body composition, including a decrease in body weight from 61.6 ± 0.9 kg to 56.5 ± 0.6 kg (P<0.001), a reduction in BMI from 25.1 ± 0.35 to 21.3 ± 0.37 (P<0.01), and a decrease in abdominal circumference from 78.96 ± 1.0 cm to 74.5 ± 1.1 cm. These changes, achieved despite the physical activity decline during the COVID-19 pandemic, highlight the effectiveness of the physical education program in addressing overweight issues and reducing central fat, akey factor in improving metabolic and cardiovascular health. The conclusions. The study demonstrates that a structured physical education program significantly enhances adolescents' physical, metabolic, and cardiovascular health, proving essential for recovery post-pandemic and prevention of chronic conditions.